APLIKASI PENGOLAHAN DATA PENJUALAN PADA PERCETAKAN CV. MITRA SIMPATI PRINTER - Pariyadi, Pariyadi; Sulisno, Witbowo (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
Data Processing Applications Sales is a data processing application that produces a variety of information that can solve the problem of process sales data in the CV. Mitra Simpati Printer. Which has been experiencing problems in inputting less accurate, less precise calculations and reports that are less efficient. Data Processing Applications Sales will help process the data and preparing reports to be more easily and accurately. The realization of Sales Data Processing Application development is the manufacture of computer applications that are able to represent information system designed as a whole. Data Processing Applications Sales generated is able to process sales data, which includes customer data, logistics data of raw materials, goods data, the data of raw materials and goods sales transaction data. Which will go through the process of inputting and calculations that are connected between each group of data well. Generate reports are complete, accurate and always actual. Results of the application design Processing Sales Data shows that the role of computer applications in the information system is very important as a support in improving the quality of sales and service activities in the corporate environment.